Unlocking the potential of stimuli-responsive biomaterials for bone regeneration - Yang, Ke; Wu, Zhuoshu; Zhang, Keke; Weir, Michael D.; Xu, Hockin H. K.; Cheng, Lei; Huang, Xiaojing; Zhou, Wen (Frontiers in Pharmacology, 2024)
Bone defects caused by tumors, osteoarthritis, and osteoporosis attract great attention. Because of outstanding biocompatibility, osteogenesis promotion, and less secondary infection incidence ratio, stimuli-responsive biomaterials are increasingly used to manage this issue. These biomaterials respond to certain stimuli, changing their mechanical properties, shape, or drug release rate accordingly. Thereafter, the activated materials exert instructive or triggering effects on cells and tissues, match the properties of the original bone tissues, establish tight connection with ambient hard tissue, and provide suitable mechanical strength. In this review, basic definitions of different categories of stimuliresponsive biomaterials are presented. Moreover, possible mechanisms, advanced studies, and pros and cons of each classification are discussed and analyzed. This review aims to provide an outlook on the future developments in stimuli-responsive biomaterials.